2016
DOI: 10.1016/j.neuropharm.2016.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian hormones, but not fluoxetine, impart resilience within a chronic unpredictable stress model in middle-aged female rats

Abstract: Depression is more prevalent in women than in men, and women are at a heightened risk for depression during the postpartum and perimenopause. There is also evidence to suggest that the ovarian hormone milieu may dictate antidepressant efficacy. Thus, it is important to investigate the role of ovarian hormones in the pathogenesis of depression and in the mechanisms that may underlie antidepressant efficacy. In the present study, we used 10-month-old female Sprague-Dawley rats to examine the effects of long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 100 publications
3
31
1
Order By: Relevance
“…Estrogen supplementation has successfully alleviated depression-like symptoms in both human patients and OVX female animals (Berlanga and Flores-Ramos, 2006; Martenyi et al, 2001; Nakagawasai et al, 2009; Rachman et al, 1998; Romano-Torres and Fernandez-Guasti, 2010; Thase et al, 2005). Further, when combined with antidepressants, estrogens can potentiate the antidepressant effects (Mahmoud et al, 2016; Rasgon et al, 2007; Recamier-Carballo et al, 2012). These observations indicate that ovarian hormones critically mediate depressive-like symptoms.…”
Section: MDmentioning
confidence: 99%
“…Estrogen supplementation has successfully alleviated depression-like symptoms in both human patients and OVX female animals (Berlanga and Flores-Ramos, 2006; Martenyi et al, 2001; Nakagawasai et al, 2009; Rachman et al, 1998; Romano-Torres and Fernandez-Guasti, 2010; Thase et al, 2005). Further, when combined with antidepressants, estrogens can potentiate the antidepressant effects (Mahmoud et al, 2016; Rasgon et al, 2007; Recamier-Carballo et al, 2012). These observations indicate that ovarian hormones critically mediate depressive-like symptoms.…”
Section: MDmentioning
confidence: 99%
“…Importantly, these effects of 17β-estradiol may not translate to conditions of chronic stress exposure. Indeed, we have shown that long-term ovarian hormone deprivation in rats increased HPA axis negative feedback impairment under chronic stress exposure (Mahmoud et al, 2016), which parallels findings in MDD indicating greater negative feedback impairment in women post-menopause (Roy et al, 1986;Young et al, 1993). Therefore, we investigated the roles of ERα and ERβ in mediating the effects of estradiol on HPA axis function under chronic stress conditions.…”
Section: Introductionmentioning
confidence: 63%
“…1). The CUS protocol was adapted from published reports (Kreisel et al, 2014;R. Mahmoud et al, 2016;Wainwright et al, 2016) and stressors used are detailed in Table 1.…”
Section: Chronic Unpredictable Stressmentioning
confidence: 99%
See 2 more Smart Citations